Intertemporal choice and consumption mobility - Tullio Jappelli; Luigi Pistaferri (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
The theory of intertemporal consumption choice makes sharp predictions about the evolution of the entire distribution of household consumption, not just about its conditional mean. In the paper, we study the empirical transition matrix of consumption using a panel drawn from the Bank of Italy Survey of Household Income and Wealth. We estimate the parameters that minimize the distance between the empirical and the theoretical transition matrix of the consumption distribution. The transition matrix generated by our estimates matches remarkably well the empirical matrix, both in the aggregate and in samples stratified by education. Our estimates strongly reject the consumption insurance model and suggest that households smooth income shocks to a lesser extent than implied by the permanent income hypothesis.
urn:nbn:de:hebis:30-23408
Keywords: D52; D91; I30; 330; Consumption Dynamics; Mobility; Gesamtwirtschaftlicher Konsum; Soziale Mobilität; Schätzung; Italien